2020
DOI: 10.1590/0034-7167-2019-0038
|View full text |Cite
|
Sign up to set email alerts
|

Primary care quality and its effects on leprosy monitoring indicators

Abstract: Objectives: to evaluate the quality of primary care in leprosy control actions, to correlate effects on monitoring indicators. Methods: a cross-sectional study, conducted in Belo Horizonte, from July to September 2014. Interviews with 408 professionals were conducted through the application of a tool that assesses attributes of primary care in leprosy control actions, and monitoring indicators were calculated. Spearman correlation was used, significance level p < 0.05. Results: the overall score correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 17 publications
0
10
0
5
Order By: Relevance
“…On the latter, it is known that the quality of leprosy control actions performed by health professionals produces effects in all indicator's disease monitoring. 25 Therefore, the importance of permanent training of professionals who care for leprosy patients is unquestionable. Diagnostic resources that are simple and of rapid applicationbecome fundamental to contribute to coping with this important health problem.…”
Section: Discussionmentioning
confidence: 99%
“…On the latter, it is known that the quality of leprosy control actions performed by health professionals produces effects in all indicator's disease monitoring. 25 Therefore, the importance of permanent training of professionals who care for leprosy patients is unquestionable. Diagnostic resources that are simple and of rapid applicationbecome fundamental to contribute to coping with this important health problem.…”
Section: Discussionmentioning
confidence: 99%
“…The adequacy of the records was verified according to the indicators for duplication, completeness and consistency proposed by Romero & Cunha 16 and Abath et al 17 Duplicates were identified by analyzing the records organized by date of notification, comparing the names of the individual-case and their mother, the date of birth of the case and the date they started treatment. Based on these comparisons, cases that showed divergence were submitted to a manual review of the respective notification forms, so as to prove whether or not they were duplicated.…”
Section: Methodsmentioning
confidence: 99%
“…Duplicate cases were excluded from the study, as per the criteria defined by Abath et al, whereby duplication below 5.0% was considered acceptable. 17 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 De modo epidemiológico, o país apresenta alta endemicidade, com coeficiente de detecção anual de 12,23 casos por 100 mil habitantes, ocupando o segundo lugar em números absolutos de casos novos da hanseníase, atrás apenas da Índia. 1,19,21,22,23 Assim, ao longo das últimas décadas, o Ministério da Saúde vem empreendendo esforços por meio de estratégias de controle da hanseníase baseadas, sobretudo, em detecção precoce, início imediato, adesão e conclusão do tratamento, prevenção e manejo das incapacidades, vigilância dos contatos e educação em saúde. 24,25 Contudo, a habilidade na operacionalização dessas ações associadas aos determinantes imunológicos, genéticos e sociais de cada região, refletem-se na distribuição da disseminação da infecção de modo heterogêneo pelo Brasil.…”
Section: Introductionunclassified